i)
![( \frac{1}{4} + \frac{1}{2} )(x + 5) = \frac{1}{5} - (x - 3) ( \frac{1}{4} + \frac{1}{2} )(x + 5) = \frac{1}{5} - (x - 3)](https://tex.z-dn.net/?f=%28+%5Cfrac%7B1%7D%7B4%7D++%2B++%5Cfrac%7B1%7D%7B2%7D+%29%28x+%2B+5%29+%3D++%5Cfrac%7B1%7D%7B5%7D++-+%28x+-+3%29)
Soluções para a tarefa
Respondido por
1
Boa tarde
(1/4 + 1/2)*(x + 5) = 1/5 - (x - 3)
(1/4 + 2/4)*(x + 5) = 1/5 - (x - 3)
3x/4 + 15/4 = 1/5 - x + 3
mmc = 20
15x + 75 = 4 - 20x + 60
35x = 64 - 75
35x = -11
x = -11/35
(1/4 + 1/2)*(x + 5) = 1/5 - (x - 3)
(1/4 + 2/4)*(x + 5) = 1/5 - (x - 3)
3x/4 + 15/4 = 1/5 - x + 3
mmc = 20
15x + 75 = 4 - 20x + 60
35x = 64 - 75
35x = -11
x = -11/35
Perguntas interessantes
Sociologia,
11 meses atrás
Matemática,
11 meses atrás
ENEM,
11 meses atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás